Literary Paternity, Literary Friendship Essays in Honor of Stanley Corngold - Richter, Gerhard (UNC Studies in the Germanic Languages and Literatures, 2002)
The twenty-one original essays in this volume offer a rigorous reconsideration of modern forms of paternity and friendship as they emerge in works by writers and philosophers from the eighteenth through the twentieth century. Exploring various models of these twin themes, contributors examine writings of canonical figures such as Goethe, Schiller, Hölderlin, Kleist, and Brentano, as well as Kafka, Benjamin, and Arendt. Together, the essays combine an emphasis on the German literary-philosophical tradition with comparative approaches, offering both theoretical discussions and sophisticated readings of crucial texts that have helped shape our contemporary literary engagement with paternity and friendship. This collection honors Stanley Corngold, an influential scholar and teacher who taught German at Princeton University for more than forty years.